Intramuscular cobinamide versus saline for treatment of severe hydrogen sulfide toxicity in swine. (4th March 2019) - Ng, Patrick C.; Hendry-Hofer, Tara B.; Garrett, Norma; Brenner, Matthew; Mahon, Sari B.; Maddry, Joseph K.; Haouzi, Philippe; Boss, Gerry R.; Gibbons, Thomas F.; Araña, Allyson A.; Bebarta, Vikhyat S.
Abstract: Introduction: Hydrogen sulfide (H2 S) is found in petroleum, natural gas, and decaying organic matter. Terrorist groups have attempted to use it in enclosed spaces as a chemical weapon. Mass casualty scenarios have occurred from industrial accidents and release from oil field sites. There is no FDA approved antidote for sulfide poisoning. We have previously reported that intravenous cobinamide is effective for sulfide poisoning. A rapid-acting antidote that is easy to administer intramuscularly (IM) would be ideal for use in a prehospital setting. In this study, we assessed survival in sulfide-poisoned swine treated with IM cobinamide. Methods: Eleven swine (45–55 kg) were anesthetized, intubated, and instrumented with continuous femoral and pulmonary artery pressure monitoring. After stabilization, anesthesia was adjusted such that animals ventilated spontaneously with a FiO2 of 0.21. Sodium hydrosulfide (NaHS, 8 mg/mL) was infused intravenously at 0.9 mg/kg.min until apnea or severe hypotension. Animals were randomly assigned to receive cobinamide (4 mg/kg), or no treatment at the apnea/hypotension trigger. The NaHS infusion rate was sustained for 1.5 min post trigger, decreased to 0.2 mg/kg.min for 10 min, and then discontinued. Results: The amount of NaHS required to produce apnea or hypotension was not statistically different in both groups (cobinamide: 9.0 mg/kg ±6.1; saline: 5.9 mg/kg ±5.5; mean difference: −3.1, 95% CI: −11.3, 5.0). All of the cobinamide treated animals survived (5/5), none of the control (0/6) animals survived ( p < .01). Mean time to return to spontaneous ventilation in the cobinamide treated animals was 3.2 (±1.1) min. Time to return to baseline systolic blood pressure (±5%) in cobinamide-treated animals was 5 min. Conclusion: Intramuscular cobinamide was effective in improving survival in this large swine model of severe hydrogen sulfide toxicity.